The Influence of Principal’s Academic Supervision, the Role of Motivator Teachers, and Teachers’ Work Discipline on School Quality at Public Elementary Schools - Memik Nor Fadilah; Maryanto Maryanto; Ngasbun Egar (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study aims to examine the influence of principal academic supervision, the role of teacher leaders (Guru Penggerak), and teacher work discipline on the quality of elementary schools in Gunungpati District, Semarang City. Employing a quantitative approach with an ex post facto method and correlational design, the research involved a total population of 270 public elementary school teachers across 32 schools. A sample of 161 teachers was selected through proportional random sampling. Data were collected using a closed-ended questionnaire measured on a Likert scale and tested for validity and reliability using SPSS software. Data analysis techniques included prerequisite tests (normality, linearity, multicollinearity, and heteroscedasticity) and hypothesis testing through multiple linear regression analysis. The findings indicate that principal academic supervision significantly influenced school quality with a contribution of 65.5%; the role of teacher leaders contributed 56.1%; and teacher work discipline contributed 59.2%. Simultaneously, the three variables accounted for 75.5% of the variance in school quality. These results demonstrate that internal school factors play a crucial role in achieving educational quality. The study underscores the importance of optimizing the principal's supervisory role, strengthening teacher leadership capacity, and fostering a disciplined work culture among teachers. The findings provide empirical evidence that can inform policy and strategic decisions to improve school quality at the institutional and systemic levels.